Books Completed or in Progress by Academy Members (Academy of Management Journal, 1964)
The article presents a list of books on management. They include “Quantitative Methods: A Survey and Guide for Managers,” Management of Industrial Enterprise,” by Richard N. Owens, “Pattern in Organization Analysis: A Critical Examination,” by Sherman R. Krupp, “Life Insurance Agency Financial Management,” by Thomas Luck and Armand Stalnaker.